Exaggerated Ventilator-Induced Lung Injury in an Animal Model of Type 2 Diabetes Mellitus: A Randomized Experimental Study - Schranc, Álmos; Fodor, Gergely H.; Südy, Roberta; Tolnai, József; Babik, Barna; Peták, Ferenc (Frontiers in Physiology, 2022)
Although ventilator-induced lung injury (VILI) often develops after prolonged mechanical ventilation in normal lungs, pulmonary disorders may aggravate the development of adverse symptoms. VILI exaggeration can be anticipated in type 2 diabetes mellitus (T2DM) due to its adverse pulmonary consequences. Therefore, we determined whether T2DM modulates VILI and evaluated how T2DM therapy affects adverse pulmonary changes. Rats were randomly assigned into the untreated T2DM group receiving low-dose streptozotocin with high-fat diet (T2DM, n = 8), T2DM group supplemented with metformin therapy (MET, n = 8), and control group (CTRL, n = 8). In each animal, VILI was induced by mechanical ventilation for 4 h with high tidal volume (23 ml/kg) and low positive end-expiratory pressure (0 cmH2O). Arterial and venous blood samples were analyzed to measure the arterial partial pressure of oxygen (PaO2), oxygen saturation (SaO2), and the intrapulmonary shunt fraction (Qs/Qt). Airway and respiratory tissue mechanics were evaluated by forced oscillations. Lung histology samples were analyzed to determine injury level. Significant worsening of VILI, in terms of PaO2, SaO2, and Qs/Qt, was observed in the T2DM group, without differences in the respiratory mechanics. These functional changes were also reflected in lung injury score. The MET group showed no difference compared with the CTRL group. Gas exchange impairment without significant mechanical changes suggests that untreated diabetes exaggerates VILI by augmenting the damage of the alveolar–capillary barrier. Controlled hyperglycemia with metformin may reduce the manifestations of respiratory defects during prolonged mechanical ventilation.